State Pythagoras theorem and its converse.
Answer
Verified
502.2k+ views
Hint: Drop a perpendicular from B to side AC in \[\Delta ABC\] right angled at B and then use similarity of triangles.
Complete step-by-step solution -
Here, we have to state and prove the Pythagoras theorem and its converse. Pythagoras Theorem states that “In a right-angled triangle, the square of hypotenuse side is equal to sum of square of other two sides”
Here, is a right-angled triangle,
According to Pythagoras Theorem,
\[{{\left( \text{Perpendicular} \right)}^{2}}+{{\left( \text{Base} \right)}^{2}}={{\left( \text{Hypotenuse} \right)}^{2}}\]
\[{{\left( AB \right)}^{2}}+{{\left( BC \right)}^{2}}={{\left( AC \right)}^{2}}\]
Now, to prove Pythagoras theorem, we will take a right- angled triangle ABC.
First, we have to drop a perpendicular BD onto the side AC.
Now in \[\Delta ADB\] and \[\Delta ABC\],
\[\angle A=\angle A\]\[\left[ \text{Common Angles} \right]\]
\[\angle BDC=\angle ABC={{90}^{o}}\]
Therefore, \[\Delta ADB\] is similar to \[\Delta ABC\] by Angle-Angle or AA criteria.
Therefore, by condition of similarity that the ratio of corresponding sides are equal.
We get, \[\dfrac{AD}{AB}=\dfrac{AB}{AC}\]
By cross multiplication, we get,
\[A{{B}^{2}}=AD.AC.....\left( i \right)\]
Also, in \[\Delta BDC\] and \[\Delta ABC\]
\[\angle C=\angle C\]\[\left[ \text{Common Angles} \right]\]
\[\angle BDC=\angle ABC={{90}^{o}}\]
Therefore, \[\Delta BDC\] is similar to \[\Delta ABC\] by Angle-Angle or AA criteria.
Therefore, by condition of similarity that the ratio of corresponding sides are equal, we get,
\[\dfrac{CD}{BC}=\dfrac{BC}{AC}\]
By cross multiplication, we get,
\[B{{C}^{2}}=CD.AC....\left( ii \right)\]
By adding equations (i) and (ii), we get,
\[A{{B}^{2}}+B{{C}^{2}}=AD.AC+CD.AC\]
By taking AC common from RHS, we get,
\[A{{B}^{2}}+B{{C}^{2}}=AC\left( AD+CD \right)\]
By diagram, we can see that,
\[AD+CD=AC\]
Therefore we get,
\[A{{B}^{2}}+B{{C}^{2}}=A{{C}^{2}}\]
Hence, Pythagoras theorem is proved.
Now, converse of Pythagoras theorem states that “if square of a side is equal to the sum of square of the other two sides then triangle must be right angled triangle”
Now, in converse of Pythagoras Theorem, we are given that if the length of sides of triangle is a, b, c and \[{{c}^{2}}={{a}^{2}}+{{b}^{2}}\], then we have to prove that triangle is right-angled triangle.
As we have already proved the Pythagoras theorem, here we will use its result.
In \[\Delta ABC\], by Pythagoras theorem
\[A{{B}^{2}}=A{{C}^{2}}+B{{C}^{2}}={{b}^{2}}+{{a}^{2}}.....\left( i \right)\]
Now, to prove the converse of Pythagoras theorem, construct another triangle, \[\Delta EGF\], such that AC = EG = b and BC = FG = a.
In \[\Delta EGF\], by Pythagoras theorem,
\[E{{F}^{2}}=E{{G}^{2}}+F{{G}^{2}}={{b}^{2}}+{{a}^{2}}.....\left( ii \right)\]
From equation (i) and (ii), we have
\[E{{F}^{2}}=A{{B}^{2}}\]
\[\Rightarrow EF=AB\]
Since, BC = FG = a
\[CA=GE=b\]
And we have proved that AB = EF = c.
Therefore, \[\Delta ACB\] is congruent to \[\Delta EGF\].
Since, we know that in \[\Delta ABC\], C is the right angle.
Therefore, in \[\Delta EFG\], G is also right angled because corresponding parts of congruent triangles are equal.
\[\Rightarrow \angle G\] is right angle
Hence, the converse of Pythagoras theorem is also proved.
Note: Students often make mistakes by assuming AA or AAA criteria as the criteria of congruence of triangles, but it is actually the criteria for similarity of triangles.
Complete step-by-step solution -
Here, we have to state and prove the Pythagoras theorem and its converse. Pythagoras Theorem states that “In a right-angled triangle, the square of hypotenuse side is equal to sum of square of other two sides”
Here, is a right-angled triangle,
According to Pythagoras Theorem,
\[{{\left( \text{Perpendicular} \right)}^{2}}+{{\left( \text{Base} \right)}^{2}}={{\left( \text{Hypotenuse} \right)}^{2}}\]
\[{{\left( AB \right)}^{2}}+{{\left( BC \right)}^{2}}={{\left( AC \right)}^{2}}\]
Now, to prove Pythagoras theorem, we will take a right- angled triangle ABC.
First, we have to drop a perpendicular BD onto the side AC.
Now in \[\Delta ADB\] and \[\Delta ABC\],
\[\angle A=\angle A\]\[\left[ \text{Common Angles} \right]\]
\[\angle BDC=\angle ABC={{90}^{o}}\]
Therefore, \[\Delta ADB\] is similar to \[\Delta ABC\] by Angle-Angle or AA criteria.
Therefore, by condition of similarity that the ratio of corresponding sides are equal.
We get, \[\dfrac{AD}{AB}=\dfrac{AB}{AC}\]
By cross multiplication, we get,
\[A{{B}^{2}}=AD.AC.....\left( i \right)\]
Also, in \[\Delta BDC\] and \[\Delta ABC\]
\[\angle C=\angle C\]\[\left[ \text{Common Angles} \right]\]
\[\angle BDC=\angle ABC={{90}^{o}}\]
Therefore, \[\Delta BDC\] is similar to \[\Delta ABC\] by Angle-Angle or AA criteria.
Therefore, by condition of similarity that the ratio of corresponding sides are equal, we get,
\[\dfrac{CD}{BC}=\dfrac{BC}{AC}\]
By cross multiplication, we get,
\[B{{C}^{2}}=CD.AC....\left( ii \right)\]
By adding equations (i) and (ii), we get,
\[A{{B}^{2}}+B{{C}^{2}}=AD.AC+CD.AC\]
By taking AC common from RHS, we get,
\[A{{B}^{2}}+B{{C}^{2}}=AC\left( AD+CD \right)\]
By diagram, we can see that,
\[AD+CD=AC\]
Therefore we get,
\[A{{B}^{2}}+B{{C}^{2}}=A{{C}^{2}}\]
Hence, Pythagoras theorem is proved.
Now, converse of Pythagoras theorem states that “if square of a side is equal to the sum of square of the other two sides then triangle must be right angled triangle”
Now, in converse of Pythagoras Theorem, we are given that if the length of sides of triangle is a, b, c and \[{{c}^{2}}={{a}^{2}}+{{b}^{2}}\], then we have to prove that triangle is right-angled triangle.
As we have already proved the Pythagoras theorem, here we will use its result.
In \[\Delta ABC\], by Pythagoras theorem
\[A{{B}^{2}}=A{{C}^{2}}+B{{C}^{2}}={{b}^{2}}+{{a}^{2}}.....\left( i \right)\]
Now, to prove the converse of Pythagoras theorem, construct another triangle, \[\Delta EGF\], such that AC = EG = b and BC = FG = a.
In \[\Delta EGF\], by Pythagoras theorem,
\[E{{F}^{2}}=E{{G}^{2}}+F{{G}^{2}}={{b}^{2}}+{{a}^{2}}.....\left( ii \right)\]
From equation (i) and (ii), we have
\[E{{F}^{2}}=A{{B}^{2}}\]
\[\Rightarrow EF=AB\]
Since, BC = FG = a
\[CA=GE=b\]
And we have proved that AB = EF = c.
Therefore, \[\Delta ACB\] is congruent to \[\Delta EGF\].
Since, we know that in \[\Delta ABC\], C is the right angle.
Therefore, in \[\Delta EFG\], G is also right angled because corresponding parts of congruent triangles are equal.
\[\Rightarrow \angle G\] is right angle
Hence, the converse of Pythagoras theorem is also proved.
Note: Students often make mistakes by assuming AA or AAA criteria as the criteria of congruence of triangles, but it is actually the criteria for similarity of triangles.
Recently Updated Pages
Questions & Answers - Ask your doubts
Master Class 11 Accountancy: Engaging Questions & Answers for Success
Master Class 11 Science: Engaging Questions & Answers for Success
Full Form of IASDMIPSIFSIRSPOLICE class 7 social science CBSE
In case of conflict between fundamental rights of citizens class 7 social science CBSE
What percentage of the area in India is covered by class 10 social science CBSE
Trending doubts
The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths
Why is there a time difference of about 5 hours between class 10 social science CBSE
Who was Subhash Chandra Bose Why was he called Net class 10 english CBSE
Change the following sentences into negative and interrogative class 10 english CBSE
Write a letter to the principal requesting him to grant class 10 english CBSE
Explain the Treaty of Vienna of 1815 class 10 social science CBSE